(untitled) (Global Scientific Review, 2023)
Endometrial hyperplasia is a gynecological disease characterized by the growth of the endometrium - the inner layer of the uterus, resulting in an increase in its thickness and volume. According to statistics, such a disease is diagnosed in 10-20 percent of patients. The disease develops in young women of childbearing age. With the onset of menopause, the risk of developing the disease increases several times